(untitled) (Medical Forum Monthly, 2024)
Objectives: To see the type of burns, pattern of burn injuries, burning agent, place of injury and total body surface area involved in children. Study Design: Descriptive study Place and Duration of Study: This study was carried out at Burn Unit, Social Security Hospital, Islamabad from January 2006 to March 2014. Materials and Methods: Children below 16 years of age reporting to causality department with burns were included in the study. Results: Among 112 patients, 17.85% and 16.96% were from 5 – 6 and 3 - 4 year of age respectively. Flame injuries were commonest (41.07%), followed by hot liquids (31.25%) and electric burns (16.07%). Majority (74.11%) of burn injuries sustained at home. 39.28% and 20.54% sustained less then 10% and 11-20% of burns respectively. Only 8.04% and 5.36% sustained burns between 21-30% and 31-40% respectively. No mortality was observed in patients having less than 40% of burns and 100% mortality among patients having more than 80% burns. Conclusion: Burn injuries from hot liquid are common in less than 6 years of age and flame burns above 10 years of age while playing with burning shopping bags and working in kitchen. As most of these injuries are avoidable, intensive educational programmes are needed to increase public awareness regarding burn dangers and to teach them how to take proper preventive and safety measures at home.